How the Awakening into Freedom and Aesthetic Self-Determination Began: Onset of the Mass Culture (KULT_online, 2013)
Since the establishment of an educational system at the turn of the 19th century, which included all parts of the society and, thus, absorbed and determinated the (previously) private sphere, we are accompanied by a constant fear about our civilized behaviour and culture. This worry manifests itself in a form of care about the future cultural agents – about the "children, we don`t know anything about" (see p. 333). We try to educate aesthetically and morally but, by doing this, we act very anxiously and superficially. Instead of a true education we tend to blame certain media for our failure, we struggle for power and over generational issues. Kasper Maase's book Die Kinder der Massenkultur gives us, from the perspective of cultural studies, a glimpse of the struggle over products and the practices of mass culture that were identified as disposable during the time of the German Empire (1871-1918). Further it shows that worries about a proper transfer and proliferation of culture have not changed that much. The continuity of the dispute about trash/high culture and its regulative and disciplining claims make the look at the German struggle about mass culture even more exciting and relevant.